2015
DOI: 10.1101/pdb.top085928
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Focusing Microscopy

Abstract: Axial localization of multiphoton excitation to a single plane is achieved by temporal focusing of an ultrafast pulsed excitation. We take advantage of geometrical dispersion in an extremely simple experimental setup, where an ultrashort pulse is temporally stretched and hence its peak intensity is lowered outside the focal plane of the microscope. Using this strategy, out-of-focus multiphoton excitation is dramatically reduced, and the achieved axial resolution is comparable to line-scanning multiphoton micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, the high frame rate needed for dynamic biological observation has motivated the development of MPE microscopy toward highthroughput configurations [8]. Temporal focusingbased multiphoton excitation microscopy (TFMPEM) provides direct widefield TPEF imaging [15][16][17][18][19], in which the diffraction element (e. g., a blazed grating) separates different spectral components of ultrashort laser pulses into different angles according to the diffraction equation and induces spatial dispersion that broadens the laser pulse width. In the so-called 4-f system setup, the diverse spectral components temporally overlap in phase only at the focal plane of the objective lens.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high frame rate needed for dynamic biological observation has motivated the development of MPE microscopy toward highthroughput configurations [8]. Temporal focusingbased multiphoton excitation microscopy (TFMPEM) provides direct widefield TPEF imaging [15][16][17][18][19], in which the diffraction element (e. g., a blazed grating) separates different spectral components of ultrashort laser pulses into different angles according to the diffraction equation and induces spatial dispersion that broadens the laser pulse width. In the so-called 4-f system setup, the diverse spectral components temporally overlap in phase only at the focal plane of the objective lens.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that a moderate increase in repetition rate does not adversely affect photobleaching characteristics, but rather significantly enhances the fluorescence signal. Increasing the repetition rate, in our hands, allowed for the implementation of a setup while solely using off-the-shelf components [34]. Nevertheless, this setup was capable of acquiring clear readouts of neuronal activity from live C. elegans animals under aversive stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the improvement of temporal resolution in LSTPM is at the cost of axial resolution, since the beam is focused only along one spatial dimension [ 12 ]. Thus, line scanning temporal focusing microscopy (LSTFM) was developed, which has the capability of parallel excitation while maintaining tight axial confinement by spatio-temporal focusing [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, with the increase in penetration depth, the accumulated wavefront distortions would deteriorate axial confinement of the excitation light.…”
Section: Introductionmentioning
confidence: 99%